Mast cells and immunoexpression of FGF-1 and Ki-67 in rat subcutaneous tissue following the implantation of Biodentine and MTA Angelus - da Fonseca, T. S.; Silva, G. F.; Guerreiro-Tanomaru, J. M.; Sasso-Cerri, E.; Tanomaru-Filho, M.; Cerri, P. S. (Wiley, 2018)
Aim: To compare the formation of fibrous capsules around Biodentine and MTA Angelus implants as well as the participation of fibroblast growth factor-1 (FGF-1) and mast cells in the tissue response to these endodontic materials. Methodology: Sixty polyethylene tubes filled with Biodentine or MTA, and empty tubes (control group) were implanted into the dorsal subcutaneous tissues of male rats. After 7, 15, 30 and 60 days, the specimens were embedded in paraffin and the number of fibroblasts and mast cells was quantified in the sections stained with Masson's trichrome or Alcian Blue, respectively. FGF-1 and Ki-67 were detected by immunohistochemistry, and the number of immunolabelled cells was computed. The collagen content was estimated in the picrosirius red-stained sections. The data were subjected to two-way ANOVA followed by Tukey's test (P ≤ 0.05). Results: The capsules were associated with a significant increase (P < 0.0001) in the number of fibroblasts and mast cells, and in the collagen content over time. A significant decrease (P < 0.0001) in the immunoexpression of FGF-1 and Ki-67 was observed in all groups from the 7th-60th day. At 60 days, the number of fibroblasts (P = 0.0226) and the collagen content (P < 0.0001) were significantly greater in MTA than Biodentine specimens, while the greatest number of mast cells and FGF-1-immunolabelled cells was observed in Biodentine specimens (P < 0.0001). A significant difference in Ki-67 immunoexpression was not detected between specimens of Biodentine and MTA. Conclusions: The collagen-rich capsule formed slowly around Biodentine in comparison with MTA. FGF-1 and mast cells participated in capsule remodelling, stimulating fibroblast proliferation and subsequent collagen production, in response to subcutaneous implants.
Keywords: Biocompatibility; Cell proliferation; Collagen; Fibroblast growth factor-1; Immunohistochemistry; Mast cells